PERANCANGAN SISTEM PENJUALAN AYAM BROILER PADA PERUSAHAAN RUMAH POTONG AYAM PUTRA DEWI SAMUDRA DI JATIWANGI - Agus Yudianto; Robbani Nida (BBM (Buletin Bisnis & Manajemen), 2016)
Sales System Broiler Chickens Rumah Potong Ayam Putra Dewi Samudra is a design system that records sales of sales transactions chicken, chicken purchase transaction, the addition of employee data, additional data supplier, sales reports and statements chicken chicken  purchases . System development method used to build this application is the waterfall mode . Whereas at this stage of the analysis and design of the system is done with tersktruktur approach. Analysis of the results of the data collection system based on the method of observation, interview, and literature study. The design of the system outlined by designing Activity Diagram, Entity Relationship Diagram (ERD), interface design, process design, and the design output. The implementation phase of this chicken sales system using VB.Net programming language. Thus the sales system can help sales data in the Rumah Potong Ayam Putra Dewi Samudra.Keywords: sales system , vb.net